Deoxysugars in glycopeptide antibiotics: Enzymatic synthesis of TDP-l-epivancosamine in chloroeremomycin biosynthesis - Chen, Huawei (The National Academy of Sciences, 2000)
The 2,3,6-trideoxysugar l-epivancosamine is the terminal sugar added to the aglycone scaffold in chloroeremomycin, a member of the vancomycin family of glycopeptide antibiotics. Five proteins from the chloroeremomycin biosynthetic cluster, ORF14 and ORF23 to ORF26, have been expressed heterologously in Escherichia coli and purified to near homogeneity, and each has been characterized for an enzymatic activity. These five enzymes reconstitute the complete biosynthesis of TDP-l-epivancosamine from TDP-4-keto-6-deoxy-d-glucose. This process involves C-2 deoxygenation, C-3 amination and methylation, C-5 epimerization, and C-4 ketoreduction. Intermediates and the final product of this pathway have been identified by mass spectrometry and NMR. The pathway established here represents the complete in vitro reconstitution of an unusual sugar for an important class of antibiotics and sets the groundwork for future combinatorial biosynthesis for new bioactive compounds.